Applying GQM method in Balanced Scorecard System for Iranian university performance appraisal: Case Study - bakhtiari, shaghayegh (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
Rapid development in academic instruction sector has resulted in changes in the supply and demand of higher education graduates and influenced on the quality of education. Hence, if the performance assessment of a university is done in an effective manner, the university may identify internal strong and weak points and provide the chance of improvement. The aim of this article is to apply Balanced Scorecard Systems to access the performance of a sample in Irans universities. On the other hand, this article describes how to apply GQM method to obtain the suitable metrics of measurement in Balanced Scorecard System assessment to improve the efficiency.